(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2022)
Purpose: The aims of this study was to determine risk factor of amblyopia in malagasy children. Methods: It was a case-control study doing at Hospital University Joseph Ravoahangy Andrianavalona from 1st september to 01st february 2022. The case were children who had functional amblyopia. The control were children who didn’t have amblyopia and came to the hospital for vision anomaly and had a similar demography specificity like case. The number of controls was twice the number of cases. All children with organic ophthalmic pathologies were excluded. The data was processed by Epi.info 7.0 software. We used Odds Ratio (OR) test to find association between amblyopia and risk factor. Confidence interval (CI) was fixed at 95%. Association was significant for a value of p<0,05. Results: 38 cases was found for 76 controls. A significant association was found for amblyopia and personnal history OR:4.85CI[1.87-12.58]p<0,00 ; familial history OR :4,84CI[2,02-11,59]p<0,00 ; for esotropia OR :6,60CI[2,62-16,56]p<0,00 ; for exotropia OR :3,07CI[1,21-7,75]p<0,01 ; for anisometropia OR :26,90CI[5,73-126.16]p<0,00 ; for hyperopia OR:4,16CI[1,69-10,25]p<0,0 and for astigmatism OR :0,22CI[0,08-0,57]p<0,00. Conclusion: Functional amblyopia was associated in children with personal and family history of strabismus and ametropia. Children with esotropia, exotropia, hyperopia, astigmatism, and anisometropia was associated with functional amblyopia. A systematic vision field is necessary for patient with risk factor.